Dr. Julien Serri — Deep Plane Facelift — Marseille - Serri, Julien (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Julien Serri, practicing in Marseille, France. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003212; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; france; marseille